Proton-pump inhibitor omeprazole attenuates hyperoxia induced lung injury. Issue 1 (December 2016) - Richter, Jute; Jimenez, Julio; Nagatomo, Taro; Toelen, Jaan; Brady, Paul; Salaets, Thomas; Lesage, Flore; Vanoirbeek, Jeroen; Deprest, Jan
Abstract Background The administration of supplemental oxygen to treat ventilatory insufficiency may lead to the formation of reactive oxygen species and subsequent tissue damage. Cytochrome P4501A1 (CYP1A1) can modulate hyperoxic lung injury by a currently unknown mechanism. Our objective was to evaluate the effect of administration of omeprazole on the induction of CYP1A1 and its influence on hyperoxic lung injury in an established preterm rabbit model. Methods Omeprazole was administered either (1) directly to the fetus, (2) to the mother or (3) after birth to the pups in different doses (2–10 or 20 mg/kg). Controls were injected with the same amount of saline. Pups were housed in normoxia (21 %) or hyperoxia (>95 %) for 5 days. Outcome parameters were induction of CYP1A1 measured by real-time polymerase chain reaction (RT-PCR) immediately after delivery, at day 3 and day 5 as well as lung function, morphometry and immunohistochemistry assessed at day 5 of life. Transcriptome analysis was used to define the targeted pathways. Results Daily neonatal injections demonstrated a dose-dependent increase in CYP1A1. Lung function tests showed a significant improvement in tissue damping, tissue elasticity, total lung capacity, static compliance and elastance. Morphometry revealed a more developed lung architecture with thinned septae in animals treated with the highest dose (20 mg/kg) of omeprazole. Surfactant protein B, vascular endothelial growth factor and its receptor were significantly increased on immunohistochemical stainings after omeprazole treatment. Conclusions Neonatal administration of omeprazole induces CYP1A1 in a dose-dependent matter and combined pre- and postnatal administration attenuates hyperoxic lung injury in preterm rabbits, even with the lowest dose of omeprazole without clear CYP1A1 induction.